Regenerative : Regenerative Development as a pathway for church renewal - Dewerse, Rosemary; Haines, Roxanne; McGregor, Stu (Ecclesial Futures, 2023)
This article details and discusses Regenerative Development, a concept developed by the Regenesis Group, as a means for enabling church health and renewal. Across 2020-2023 Cityside Baptist in Auckland, Aotearoa New Zealand, worked with Regenerative Development Practitioners through three phases of application. The process and what emerged challenges usual perspectives on church growth and revitalisation priorities around vision, outcomes and the community and context in view. In the first version the captions of figures 2 and 3 had been swapped, which has been corrected in version 2.